2022
DOI: 10.3390/ma15196856
|View full text |Cite
|
Sign up to set email alerts
|

Eutectic Fatty Acids Phase Change Materials Improved with Expanded Graphite

Abstract: Low- and ultra-low-grade thermal energy have significant recycling value for energy saving and carbon footprint reduction. Efficient thermal energy storage technology based on phase change materials (PCMs) will help improve heat recovery. This study aimed to develop a composite eutectic fatty acid of lauric acid (LA) and stearic acid (SA) binary system with expanded graphite (EG). The experimental measured eutectic temperature was 31.2 °C with an LA-to-SA mass ratio of 7:3. Afterwards, 1~15 wt.% EG was composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…In the open literature, despite the existence of several works investigating the stabilization of PCMs within EG, the reported thermal conductivity values are generally low (from less than 1 W/(m K) [30,31] to 2.1 W/(m K) [32], rarely exceeding this value [29], along with the use of EG unless its fraction is higher than the PCM one [16]), and the PCM amount is limited to values below certain thresholds in order to avoid leaking (also below 70 wt.% [32]) with consequent complications in the production process and limitations in the use phase. In some works, thermal conductivity is enhanced only of less than 400% even with the addition of 20 wt.% EG [33].…”
Section: Introductionmentioning
confidence: 99%
“…In the open literature, despite the existence of several works investigating the stabilization of PCMs within EG, the reported thermal conductivity values are generally low (from less than 1 W/(m K) [30,31] to 2.1 W/(m K) [32], rarely exceeding this value [29], along with the use of EG unless its fraction is higher than the PCM one [16]), and the PCM amount is limited to values below certain thresholds in order to avoid leaking (also below 70 wt.% [32]) with consequent complications in the production process and limitations in the use phase. In some works, thermal conductivity is enhanced only of less than 400% even with the addition of 20 wt.% EG [33].…”
Section: Introductionmentioning
confidence: 99%
“…Zanshe Wang et al. prepared fatty acid/EG composites and successfully increased thermal energy storage efficiency [28] . Ci Ao et al.…”
Section: Introductionmentioning
confidence: 99%
“…Zanshe Wang et al prepared fatty acid/EG composites and successfully increased thermal energy storage efficiency. [28] Ci Ao et al prepared SA/EG composites and revealed that more loading amount of EG in SA/EG composites supported higher thermal conductivity of SA/EG composites. [29] After optimizing PCM/EG composites with maximum PCM loading amount, PCM/EG composites are aimed for various applications.…”
Section: Introductionmentioning
confidence: 99%
“…Energy storage technology is one of the effective methods to solve the energy crisis, and it has broad application prospects in the fields of shifting peaks and valleys of power, solar energy utilization, industrial waste heat recycling, building heating, and air conditioning. Thermal energy storage can generally be divided into chemical energy storage, sensible heat storage, and latent heat storage. , Latent heat storage has many advantages, including high energy storage density, low temperature change, excellent material stability, and high safety, so it has received a significant amount of attention and application. Fatty acids have attracted much attention for their appropriate phase change temperature, high phase change latent heat, nontoxicity, noncorrosiveness, no or small volume change, small degree of subcooling, good thermal reliability, abundant raw materials, easily obtainable, and other advantages. , More importantly, two or more fatty acids can be mixed into a eutectic mixture according to the eutectic effect of fatty acids to reduce the phase change temperature and expand its temperature application range. , Although fatty acid eutectic mixtures have many advantages, they also have the disadvantages of poor thermal conductivity and easy leakage. At present, the common method to solve these problems is to add materials with high thermal conductivity and porous structures to fatty acid PCMs. Due to its low density, high thermal conductivity, and porous structure, expanded graphite (EG) is frequently utilized as a substrate material, which not only minimizes liquid leakage but also significantly improves the thermal conductivity of the PCMs. …”
Section: Introductionmentioning
confidence: 99%